2023
DOI: 10.3390/app13020686
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain for the Healthcare Supply Chain: A Systematic Literature Review

Abstract: A supply chain (SC) is a network of interests, information, and materials involved in processes that produce value for customers. The implementation of blockchain technology in SC management in healthcare has had results. This review aims to summarize how blockchain technology has been used to address SC challenges in healthcare, specifically for drugs, medical devices (DMDs), and blood, organs, and tissues (BOTs). A systematic review was conducted by following the PRISMA guidelines and searching the PubMed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…A qualitative study can explore the topics of research that have not been studied or understood thoroughly. For a thorough qualitative study, an in-depth review of existing literature helps the researcher to identify relevant issues about the research topic of inquiry [35].…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative study can explore the topics of research that have not been studied or understood thoroughly. For a thorough qualitative study, an in-depth review of existing literature helps the researcher to identify relevant issues about the research topic of inquiry [35].…”
Section: Methodsmentioning
confidence: 99%
“…This technology has the potential to reduce operating costs and increase synergies while preserving the integrity of data [56]. In [57], a systematic review was conducted to summarize how blockchain technology has been used to address supply chain challenges in healthcare. The findings of the review indicated a significant but immature interest in the topic, with diverse ideas and methodologies but without effective real-life applications.…”
Section: Related Workmentioning
confidence: 99%
“…Issues related to low throughput and low scalability, which limit its adoption in the healthcare industry [57] A systematic review Summarizing how blockchain technology has been used to address supply chain challenges in healthcare.…”
Section: Sharing Data Among Different Local Blockchain Network (Diffe...mentioning
confidence: 99%
“…Additionally, Africa's export industry is also making a considerable impact, recording a market share of 5.3%. Meanwhile, Australia recorded a share of 1.4%, and the Americas have experienced a moderate rise in their export [28].…”
Section: World Trade Organisation (Wto)mentioning
confidence: 99%